2021
DOI: 10.1029/2020tc006515
|View full text |Cite
|
Sign up to set email alerts
|

Response of Surface Erosion to Crustal Shortening and its Influence on Tectonic Evolution in Fold‐and‐Thrust Belts: Implications From Sandbox Modeling on Tectonic Geomorphology

Abstract: The interaction between structural deformation and geomorphic processes is an active research topic in earth system sciences (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 91 publications
(158 reference statements)
3
14
0
Order By: Relevance
“…The redistribution of mass in CR 0.19 0 results in an increase in the thrust spacing and consequently in the width of the wedge (e.g., Fillon et al, 2013;Storti & McClay, 1995). Mao et al (2021) found a good correlation between lower shortening rates and longer intervals between structures, assessing that the thickness of sediments opposes the displacement of the thrusts.…”
Section: Mass Redistribution Controls Wedge Morphologymentioning
confidence: 95%
“…The redistribution of mass in CR 0.19 0 results in an increase in the thrust spacing and consequently in the width of the wedge (e.g., Fillon et al, 2013;Storti & McClay, 1995). Mao et al (2021) found a good correlation between lower shortening rates and longer intervals between structures, assessing that the thickness of sediments opposes the displacement of the thrusts.…”
Section: Mass Redistribution Controls Wedge Morphologymentioning
confidence: 95%
“…In active fold-thrust belts around the world, such as the Aconcagua fold-thrust belt in Argentina (Hilley et al, 2004), the central Andes fold-thrust belt in Bolivia (Horton, 1999;McQuarrie et al, 2008), the central Apennines fold-thrust belt in Italy (Scisciani and Montefalcone, 2006;Wu and McClay, 2011), and the Taiwan fold-thrust belt in China (Dahlen and Suppe 1988;Dadson et al, 2003;Wu and McClay, 2011), the roles of different synkinematic erosion and/or sedimentary loading, probably caused by long-term along-strike climatic variations (McQuarrie et al, 2008), on the generation and evolution of thrust faults in these fold-thrust belts (thrust wedges) have been interpreted and discussed by the Coulomb wedge model theory (e.g., Davis et al, 1983;Dahlen et al, 1984;Dahlen and Suppe 1988) and experimental simulations (e.g., Storti and Mcclay, 1995;Persson and Sokoutis, 2002;Simpson, 2006;Graveleau and Dominguez, 2008;Cruz et al, 2010;Cruz et al, 2011;Wu and McClay, 2011;Malavieille, 2011;Steer et al, 2014;Sun et al, 2016;Sun et al, 2021;Luo et al, 2021;Mao et al, 2021). Theoretical analysis and modeling results have all shown that syntectonic erosion reduced the number of major forwardvergent thrusts, and increased exhumation and thrust activities at the rear of the thrust wedge, resulted in out-of-sequence thrusting and fault reactivation in the wedge hinterland, and inhibited the forward propagation of the deformation front into the foreland.…”
Section: Influence Of Erosion and Sedimentary Loading On Activity Of Thrust Faults In Lmsmentioning
confidence: 99%
“…Moreover, in the LMS foldthrust belt, Li et al (2016), Li C. et al (2018) identified growth strata and revealed early to late Pleistocene activity on the Range Front blind thrust. Recently, by using sandbox analog experiments, Luo et al (2021) investigated the influences of differential rates of synkinematic erosion and sedimentation on wedge geometries and fault activities during the development of thrust wedges, and further discussed the influences from the change of erosion-sedimentation along the strike on the structural evolution of the LMS fold-thrust belt; Mao et al (2021) have shown that surface erosion and sedimentation affected the position, morphology, lateral propagation, and connection of new structures in fold-thrust belts. Overall, sufficient studies have shown the important relationship between surface processes (denudation and/or deposition) and tectonic processes (fault activity) in fold-thrust belts, although there are still some different viewpoints on the main controlling factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneer paper of Hubbert (1937) [25], many studies have focused on analog models scaling (e.g., [19,20,[26][27][28]). Here, the scaling of our experiments was done by taking into account dynamic, geometric, and kinematic similarity criteria between model parameters and field observations.…”
Section: Scalingmentioning
confidence: 99%
“…A few previous studies combined analog and numerical approaches for studying the surface and tectonic processes at the crustal scale (e.g., [18]). This method is currently used to estimate erosion and sedimentation processes according to the granular composition [19] and the erosion influence on tectonics in a context of crustal shortening [20]. Following this approach, we investigated the evolution of a geomorphologic marker by comparing analog and numerical models.…”
Section: Introductionmentioning
confidence: 99%